E-MODUL ATTRIBUTIONAL RETRAINING UNTUK MENINGKATKAN OPTIMISME KARIR MAHASISWA - Umar, Nur Fadhilah (Universitas Nusantara PGRI Kediri, 2017)
Career optimism is an affection factor which influence the student’s achievement, motivation, self-effication, self-esteem and level of depression. Low of career optimism is a student’s problem in the last semester in university. Counselling technique which can increase student’s career optimism is attributional retraining technique. Low of counselling services for students in the university which is caused by irrelevant ratio between counselors and students encourage the researcher to develop e-Modul Attributional retraining with the intention of rising up student’s career optimism. This product is envisaged that can help students to improve their career optimism independently. Method in this research was research and development model (R&D) by Borg & Gall (1983). The stage of the research were 1) preparation, 2) Arranging initial product, 3) expert validation, 4) Revising Initial product, 5) field experiment, 6) Revising eventual product and 7) Dessemination. The Research has resulted that Attributional retraining e-Modul showed a high validity as per the expert validation by counselors and programmers. The result of product acceptance by users found out that there were score differences of student’s career optimism between pre and post stage related to the Attributional retraining e-Modul. Key Words: e-Modul, Attributional Retraining, career optimism